The F-Box Protein OsFBK12 Targets OsSAMS1 for Degradation and Affects Pleiotropic Phenotypes, Including Leaf Senescence, in Rice(1)([W])([OPEN]) - Chen, Yuan (American Society of Plant Biologists, 2013)
Leaf senescence is related to the grain-filling rate and grain weight in cereals. Many components involved in senescence regulation at either the genetic or physiological level are known. However, less is known about molecular regulation mechanisms. Here, we report that OsFBK12 (an F-box protein containing a Kelch repeat motif) interacts with S-ADENOSYL-l-METHIONINE SYNTHETASE1 (SAMS1) to regulate leaf senescence and seed size as well as grain number in rice (Oryza sativa). Yeast two-hybrid, pull-down, and bimolecular fluorescence complementation assays indicate that OsFBK12 interacts with Oryza sativa S-PHASE KINASE-ASSOCIATED PROTEIN1-LIKE PROTEIN and with OsSAMS1. Biochemical and physiological data showed that OsFBK12 targets OsSAMS1 for degradation. OsFBK12-RNA interference lines and OsSAMS1 overexpression lines showed increased ethylene levels, while OsFBK12-OX lines and OsSAMS1-RNA interference plants exhibited decreased ethylene. Phenotypically, overexpression of OsFBK12 led to a delay in leaf senescence and germination and increased seed size, whereas knockdown lines of either OsFBK12 or OsSAMS1 promoted the senescence program. Our results suggest that OsFBK12 is involved in the 26S proteasome pathway by interacting with Oryza sativa S-PHASE KINASE-ASSOCIATED PROTEIN1-LIKE PROTEIN and that it targets the substrate OsSAMS1 for degradation, triggering changes in ethylene levels for the regulation of leaf senescence and grain size. These data have potential applications in the molecular breeding of rice.